Patient-Derived Cancer-Associated Fibroblasts Support the Colonization of Tumor Cells in Head and Neck Squamous Cell Carcinoma - Julia Federspiel; Teresa Bernadette Steinbichler; Samuel Moritz Vorbach; Marie Theres Eling; Wegene Borena; Christof Seifarth; Benedikt Gabriel Hofauer; Jozsef Dudas (Biomedicines, 2025)
Background: The crosstalk between cancer-associated fibroblasts (CAFs) and tumor cells promotes proliferation, tumor relapse, and the acquisition of a partial epithelial-to-mesenchymal (pEMT) phenotype in tumor cells. The aim of this study was to investigate the effects of patient-derived CAFs on tumor cell growth and radioresistance in head and neck squamous cell carcinoma (HNSCC). Methods: CAFs were isolated and cultured in a three-dimensional spheroid formation. SCC-25 tumor cells educated by the CAFs (SCC25-E cells) were subjected to irradiation, and the response of the CAF-stimulated tumor cells to radiotherapy was determined using an MTT assay, a clonogenic assay, and Western blotting. Tumor cell morphological changes and growth dynamics were assessed using 3D holotomographic microscopy and a live video microscope. Results: Patient-derived CAFs significantly increased the growth rate of SCC-25 cells. CAFs drove fibrosis in the tumor microenvironment (TME), functioned as a physical barrier, temporarily stopped tumor growth, and induced the p38 mitogen-activated protein kinase (MAPK) signaling pathway. Viability after irradiation at 4–8 Gy was significantly higher in SCC25-E cells than in the controls (p = 8 × 10–4 or lower). Furthermore, irradiation triggered the pEMT profile in HNSCC cells. Conclusions: CAFs’ education of tumor cells and the induced p38 phosphorylation had no influence on irradiation sensitivity. SCC25-E cultures demonstrated increased tumor cell growth, viability, and stress-induced phospho-p38 activation.